2004
DOI: 10.1081/cbi-200038513
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Health and Sleep Complaints Among Nursing Personnel Working Under 12 h Night and Day Shifts

Abstract: This cross-sectional exploratory study involved health care workers of various skill types and levels. We tested the hypothesis that the prevalence of diseases, sleep complaints, and insufficient time for nonprofessional activities (family, leisure, and rest) are higher among night than day workers. Data collection was carried out in two public hospitals using questionnaires and other forms. Night work was explored as a risk factor, considering a night worker as one who had at least one night job on the occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
16

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 35 publications
2
64
0
16
Order By: Relevance
“…Data collection was based on a comprehensive instrument (about 300 questions) that considered the participants working arrangements including those from a second job (Portela et al, 2004) and the hours spent on housework per week. In addition, we also examined any informal changes in work schedules agreed to by the workers (Ribeiro-Silva et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection was based on a comprehensive instrument (about 300 questions) that considered the participants working arrangements including those from a second job (Portela et al, 2004) and the hours spent on housework per week. In addition, we also examined any informal changes in work schedules agreed to by the workers (Ribeiro-Silva et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…A second job is taken mainly due to low wages and the present work schedules which do not require consecutive working days. However, the outcome for nurses is long professional working hours (Portela et al, 2004;Borges et al, 2003;Aquino et al, 1993). These long working hours added to domestic work and childcare represent the so-called "double or triple work journey" (Aquino et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…As one manager puts it, 'Not everyone can be a team leader. ' In comparison with other shift systems, fixed night shifts impair personal relationships and mental well-being (Portela et al 2004). One worker at Amartya's firm puts it bluntly: 'I feel that my organization's working timings are very odd and that affects my social and family life … which demolishes my happiness.'…”
Section: Social and Family Problems: 'We Are Like Owls'mentioning
confidence: 99%
“…In a study among Brazil health care workers, Portela et al (Portela et al, 2004) found that mild emotional disorders were less frequent among night and ex-night workers than among day workers who never had worked in night job. The possible role of exposure by day workers to some risk factors such as work-related stress, was suggested as an explanation for the surprising results.…”
Section: Studies Not Finding Shift-work Associated With Decreased Welmentioning
confidence: 99%
“…In a sample of Brazil health care workers, Portela et al (Portela et al, 2004) found that working nights more than four times per 2-weeks was related to complaints about insufficient time for children and rest/leisure.…”
Section: Studies Supporting An Association Between Non-standard Hoursmentioning
confidence: 99%